Tropylium Ion Catalyzes Hydration Reactions of Alkynes. Issue 29 (14th June 2018) - Oss, Giulia; Ho, Junming; Nguyen, Thanh Vinh
Abstract : The hydration of alkynes is one of the most atom‐economic and versatile synthetic protocols to access carbonyl compounds. This fundamental reaction, however, often requires transition‐metal catalysts or harsh reaction conditions to promote the addition of water to the carbon–carbon triple bond. In this work, it is demonstrated that the non‐benzenoid aromatic tropylium ion can be used as an organic Lewis acid promoter for the hydration of alkynes under simple reaction conditions with excellent outcomes. Abstract : The non‐benzenoid aromatic tropylium ion can be used as an organic Lewis acid promoter for the transition‐metal‐free hydration of alkynes under simple reaction conditions with excellent outcomes.